2013
DOI: 10.7314/apjcp.2013.14.12.7595
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cervical Cancer in Rural Areas of Wuhan China: a Matched Case-control Study

Abstract: Cervical cancer is a serious public health problem in developing countries. We investigated possible risk factors for cervical cancer in rural areas of Wuhan China using a matched case-control study with 33 women diagnosed with cervical cancer and 132 healthy women selected from the same area as matched controls. A questionnaire, which included questions about general demography conditions, environmental and genetic factors, the first sexual intercourse, first marriage age, age at first pregnancy, pregnancy fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…There are many risk factors that could cause cervical carcinoma, such as sex at an early age, multiple sexual partners, multiparty, smoking, hormonal contraceptives, immunosuppression or certain infections. Among those, persistent infection of human papillomavirus (HPV) is the leading factor [1,2]. Though recently two prophylactic vaccines against the high-risk strains of HPV (HPV-16 and 18) have been developed and carried out in more than 100 countries in the world, they are not widely used in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…There are many risk factors that could cause cervical carcinoma, such as sex at an early age, multiple sexual partners, multiparty, smoking, hormonal contraceptives, immunosuppression or certain infections. Among those, persistent infection of human papillomavirus (HPV) is the leading factor [1,2]. Though recently two prophylactic vaccines against the high-risk strains of HPV (HPV-16 and 18) have been developed and carried out in more than 100 countries in the world, they are not widely used in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have revealed the result coincident with the augmentation of cervical cancer among the young women before 40 years old in certain countries (Quinn et al, 1999. Li et al, 2004Zhang et al, 2014;Wang et al, 2014;Shen et al, 2014;Du et al, 2014). The median age of the total patients with histologically confirmed CIN II-III at the time of the treatment is 35.12 years old (range 19-57), 44 women among them were diagnosed as cervical carcinoma in situ with 36.12 years old as the median age; moreover, there was no significant statistic difference at the median age between women with residual/recurrent case (34.68 years old) and non recurrent cases (35.26 years old).…”
Section: Discussionmentioning
confidence: 94%
“…In addition to breast cancer, several epidemiological studies also reported links between pregnancy characteristics and other types of cancer. These include: a) low age of first gestation increases the risk of cervical cancer (OR=13.1, 95%CI: 3.7-47.3) (Zhang et al, 2013); b) multiple births lower the risk of nonmucinous ovarian cancer (OR=0.71, 95%CI: 0.52-0.98) (Whiteman et al, 2000); c) preterm deliveries endanger women in (RR=2.3, 95%CI: 1.3-3.8) and low birth weight (RR=0.7; 95%CI:0.4-1.0) protects women from developing epithelial ovarian cancer (Mucci et al, 2007) etc. The links between DM and cancer seem to be relatively clear.…”
Section: Discussionmentioning
confidence: 99%